Effect of the Step-Jump Approach in Infected Pancreatic Necrosis: A Propensity Score-Matched Study - Bai R; Sui Y; Lu T; Chen H; Wang G; Kong R; Tan H; Wang Y; Li G; Sun B (Dove Medical Press, 2024)
Rui Bai,1,2 Yuhang Sui,1,2 Tianqi Lu,1,2 Hua Chen,1,2 Gang Wang,1,2 Rui Kong,1,2 Hongtao Tan,1,2 Yongwei Wang,1,2 Guanqun Li,1,2 Bei Sun1,2 1Department of Pancreatic and Biliary Surgery, The First Affiliated Hospital of Harbin Medical University, Harbin, 150001, People's Republic of China; 2Key Laboratory of Hepatosplenic Surgery, Ministry of Education, The First Affiliated Hospital of Harbin Medical University, Harbin, 150001, People's Republic of ChinaCorrespondence: Guanqun Li; Bei Sun, Department of Pancreatic and Biliary Surgery, The First Affiliated Hospital of Harbin Medical University, No. 23 Youzheng Street, Nangang District, Harbin, 150001, People's Republic of China, Email liguanqun@hrbmu.edu.cn; sunbei70@hrbmu.edu.cnPurpose: The effects of the step-jump approach on the survival and prognosis of infected pancreatic necrosis (IPN) patients have not yet been determined.Patients and Methods: Between November 2018 and June 2023, 188 patients were included in this study. There were 144 patients in the step-up group (the SU group) and 44 in the step-jump group (the SJ group). In the SU group, patients successfully treated with percutaneous catheter drainage (PCD) alone were classified into the SU-1 group (n=101), while those requiring additional surgery after PCD were categorized into the SU-2 group (n=43). In the SJ group, patients who underwent minimally invasive necrosectomy (MIN) without PCD were assigned to the SJ-1 group (n=34), whereas those who initially underwent PCD followed by immediate open surgery were placed in the SJ-2 group (n=10). Propensity score matching (PSM) was used to mitigate bias.Results: After PSM, a total of 34 pairs were successfully matched. A comparison of the SU group with the SJ-1 group (upfront MIN without PCD) revealed similar mortality rates (P=0.239); however, the incidences of multiple drug-resistant organisms (MDROs) (P=0.029) and surgical complications (P< 0.001) were significantly lower in the SJ-1 group. After comparing the SU-2 and SJ-2 groups (patients who underwent direct open necrosectomy without MIN after PCD failure), the incidences of surgical complications and MDRO in the SJ-2 group were significantly lower (P< 0.05).Conclusion: Compared with the step-up approach, the step-jump approach is safer and more effective and can significantly reduce the incidence of MDRO and surgical complications.Keywords: infected pancreatic necrosis, step-up approach, step-jump approach, propensity score match